Anxiety Decreases the Success of Misoprostol Induction - Dua Novita Sari; Dwi Izzati; Atika (Universitas STRADA Indonesia, 2024)
Pregnancy post term increasing the duration of waiting time for birth can cause a stress reaction in the form of anxiety. Termination of pregnancy using misoprostol in post term pregnancies is expected to result in immediate labor and end in vaginal delivery. Research analyzes the influence of anxiety experienced by pregnant women post term on the success of misoprostol induction. The research design uses prospective cohort, sampling technique consecutive sampling with a minimum sample size of 37 samples. Data collection uses questionnaires Hamilton Rating Scale for Anxiety (HRS-A). Data were analyzed univariately, followed by bivariate tests Chi Square using SPSS version 2022. The results 78.3% of pregnant women post term experiencing anxiety before giving birth, 59.5% of mothers given misoprostol gave birth vaginally.